Kajian Pastoral Holistik Kedukaan terhadap Warga Jemaat Gereja Kalimantan Evangelis (GKE) Palangka I di masa Pandemi COVID-19 - Maria Angela; Tahan M. Cambah; Max Susan (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2022)
Grief caused by the death of a family member due to the COVID-19 pandemic is often not handled with a holistic approach that includes physical, psychological, social, and spiritual factors. This research was carried out using a qualitative method and a holistic approach initiated by Howard Clinebell and J.D. Engel. This study aims to understand the situation, conditions, and needs during the mourning period and when family members are exposed to the COVID-19 virus. This research was conducted at the GKE Palangka I Congregation, Palangka Raya City. This study found that the church's pastoral approach was not holistic. The church tends to take a very minimal approach. The majority of what church administrators do is spiritual service. A holistic pastoral approach requires assistance from the church in all areas, including physical, psychological, social, and spiritual. It is this approach that church members need.